Perencanaan Dinding Penahan Tanah Concrete Cantilever Dengan Menggunakan Program Plaxis (Studi Kasus : Jalan Liwa – Simpang Gunung Kemala Krui KM.264+600) - Winanda, Restu Arga; Setyanto, Setyanto; Hadi, Yohanes Martono (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Landslides in Bukit Barisan Selatan National Park (TNBBS) usually occur during the rainy season, because the intensity of the rain more than usual, causing soil to become saturated with water in which the soil is no longer able to accommodate the water into the pores so that the pore water will rise resulting in shear strength become so small that the land becomes unstable and prone to landslides. Plaxis is a computer program based on two-dimensional finite element method that is used specifically to perform deformation and stability analysis for various applications in the geotechnical field by modeling geometry and mesh elements based on cross section. From the analysis of slope stability with a height of 10 m, the slope is expressed in critical condition. The countermeasures are carried out with three conditions, the slope with cantilevered wall strengthening B is considered safe because it has a safety factor value of 1.4953, and the smallest displacement and settlement value between two other conditions and satisfies the shear stability of 2.8200> 2 (Safe), the stability of overturning 3.9631> 2 (Safe) and soil bearing capacity is 2.2782> 2 (Safe). Keywords: slope stability, safety factor, plaxis, cantilevered retaining wall.